Association of early severe thrombocytopenia and platelet course with in-hospital mortality in critically ill children - Lu, Yan; Ren, Chaoxiang; Guo, Haoyang (Frontiers in Pediatrics, 2022)
This study aimed to assess the association of early severe thrombocytopenia and platelet course with in-hospital mortality in critically ill children. Data of critically ill children in this study were obtained from the Pediatric Intensive Care Database. Patients with and without severe thrombocytopenia were adjusted for covariates using propensity score matching (PSM) to ensure the robustness of the results. Univariate and multivariate logistic regression analyses were performed on the original and PSM cohorts, respectively. Results are presented as odds ratios (ORs) with 95% confidence intervals (95% CI). In studies of the platelet course, logistic regression analysis was used to assess the effect of different degrees of recovery on in-hospital mortality in critically ill children with early severe thrombocytopenia. The study included 4,848 critically ill children, of whom 450 with early severe thrombocytopenia were matched to 450 without early severe thrombocytopenia. Univariate and multivariate logistic regression results showed that early severe thrombocytopenia was an independent risk factor for in-hospital mortality in critically ill children in both the original and PSM groups. In addition, the study results of platelet course showed that the recovery of platelet count to ≥ 150 × 109/L in the short term was a protective factor for the prognosis of patients (OR, 0.301; 95% CI, 0.139–0.648, P=0.002). Our study revealed that early severe thrombocytopenia is an independent risk factor for in-hospital mortality in critically ill children. In addition, in-hospital mortality was significantly reduced in children with early severe thrombocytopenia, whose platelet count returned to normal levels in the short term.